Promoting Mental Health and Criminal Justice Collaboration Through System-Level Partnerships - Kamin, Don; Weisman, Robert L.; Lamberti, J. Steven (Frontiers in Psychiatry, 2022)
Recent high-profile deaths of unarmed individuals in police custody have raised concerns about the role of police officers in responding to people who are experiencing mental health crises. Of further concern, people with serious mental illness are highly over-represented throughout the entire criminal justice system including within jail, prison and community corrections populations. It is widely accepted that promoting mental health and criminal justice collaboration is a key to addressing these concerns. Promoting effective collaboration is challenging, however, due to fundamental differences in cultures and methods that exist between mental health and criminal justice service providers. To promote effective collaboration between service providers, a conceptual framework was recently published that divides the collaborative process into separate steps and outlines respective responsibilities at each step. Yet optimal collaboration between mental health and criminal justice service providers requires the support of their respective supervisors and agency heads. This paper extends previous work at the service provider level by applying the conceptual framework to promote effective collaboration at the systems level (i.e., between agencies). Barriers to inter-agency collaboration are discussed, and strategies for facilitating collaboration at each step of the collaborative process are presented.